Carta de José Celso Barbosa a Roberto H. Todd - Todd, Roberto H.; Celso Barbosa, José (My University, 1921)
Nombramiento de "Postmasters".
Keywords: Celso Barbosa, José--Correspondencia.; Celso Barbosa, José--Correspondence.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.